(ZMA)-transform method. Issue 7 (3rd October 2021) - Alwan, Zainab Mohammed
Abstract: In this action, we study a new integral transform identical to laplace, ZZ and Sumudu transforms are started. (ZMA)–Transform is asymptotic to ZZ transforms with some modification. The feature of this transform solves the differential equations (DE) smoothly and effectively without complications and with guaranteed results, moreover presented application for initial value problem (IVP) show that the transformation. In addition to this, I prepared a table for these transfers.